Replication of Aleutian mink disease parvovirus in lymphoid tissues of adult mink: involvement of follicular dendritic cells and macrophages. - Mori, S (1991)
By using strand-specific in situ hybridization and immunohistochemistry, evidence for replication of the Aleutian mink disease parvovirus was observed in cells resembling macrophages and cells resembling follicular dendritic cells at 10 days after infection but only in macrophages at 60 days. Sequestration of the Aleutian mink disease parvovirus in larger numbers of macrophages and follicular dendritic cells was noted at both 10 and 60 days.